THE ROLE OF GREEN ECONOMY IN SUSTAINABLE DEVELOPMENT: A LITERATURE REVIEW ON STRATEGIES FOR LOW-CARBON ECONOMIC TRANSITION - Tulus Pujo Nugroho (International Journal Management and Economic, 2025)
This study systematically reviews the existing literature on the role of the green economy in supporting sustainable development through low-carbon economic transition strategies. Using a Systematic Literature Review (SLR) methodology, 80 peer-reviewed articles published between 2013 and 2023 were analyzed, sourced from databases such as Scopus, Web of Science, and Google Scholar. The review identifies key strategic themes including green fiscal policy, renewable energy investment, carbon trading mechanisms, and the role of public-private partnerships in accelerating the shift toward low-carbon models. The findings highlight the relevance of green economy practices in aligning national development with global sustainability goals, especially in relation to the Sustainable Development Goals (SDGs). However, implementation challenges persist, particularly in developing countries, due to institutional, financial, and political constraints. This review provides a synthesis of best practices and research gaps, offering a foundation for future studies and policy-making that aim to integrate economic growth with environmental resilience.